The Use of Jejunal Tube Feeding in Children: A Position Paper by the Gastroenterology and Nutrition Committees of the European Society for Paediatric Gastroenterology, Hepatology, and Nutrition 2019. Issue 2 (August 2019) - Broekaert, Ilse J.; Falconer, Jackie; Bronsky, Jiri; Gottrand, Frederic; Dall'Oglio, Luigi; Goto, Eunice; Hojsak, Iva; Hulst, Jessie; Kochavi, Brigitte; Papadopoulou, Alexandra; Ribes-Koninckx, Carmen; Schaeppi, Michela; et al.
ABSTRACT: Objectives: Jejunal tube feeding (JTF) is increasingly becoming the standard of care for children in whom gastric tube feeding is insufficient to achieve caloric needs. Given a lack of a systematic approach to the care of JTF in paediatric patients, the aim of this position paper is to provide expert guidance regarding the indications for its use and practical considerations to optimize its utility and safety. Methods: A group of members of the Gastroenterology and Nutrition Committees of the European Society of Paediatric Gastroenterology Hepatology and Nutrition and of invited experts in the field was formed in September 2016 to produce this clinical guide. Seventeen clinical questions treating indications and contraindications, investigations before placement, techniques of placement, suitable feeds and feeding regimen, weaning from JTF, complications, long-term care, and ethical considerations were addressed. A systematic literature search was performed from 1982 to November 2018 using PubMed, the MEDLINE, and Cochrane Database of Systematic Reviews. Grading of Recommendations, Assessment, Development, and Evaluation was applied to evaluate the outcomes. During a consensus meeting, all recommendations were discussed and finalized. In the absence of evidence from randomized controlled trials, recommendations reflect the expert opinion of the authors. Results: A total of 33 recommendations were voted on using the nominal voting technique. Conclusions: JTF is a safe and effective means of enteral feeding when gastric feeding is insufficient to meet caloric needs or is not possible. The decision to place a jejunal tube has to be made by close cooperation of a multidisciplinary team providing active follow-up and care.